Street Children Handling Strategies Based on Regional Policies: A Qualitative Study in Ambon City - Derek Bakarbessy; Vesticha Marshanda Tamaela; Vernando Yanry Lameky (Greenation International Journal of Law and Social Sciences, 2026)
The phenomenon of street children reflects structural inequality, urban poverty, and weaknesses in the child protection system. In Ambon City, although official data indicate a decline in the number of street children between 2022 and 2025, recurring cases and contradictory practices on the ground suggest persistent implementation gaps in policy execution. This study analyses the strategies employed by the Ambon City Social Service in addressing street children within the framework of local regulations using a child rights approach and a social policy analysis perspective. A qualitative case study design was employed. Data were collected through in-depth semi-structured interviews with Social Service officials and street children, field observations in major public spaces in Ambon City, and analysis of relevant policy documents. The findings show that current strategies combine short-term outreach operations, fulfilment of basic needs, and family reintegration with longer-term rehabilitation, alternative education, and skills training programmes. However, testimonies from street children reveal the persistence of coercive practices during field operations, indicating inconsistencies between policy commitments to child-friendly governance and implementation practices. This study contributes to the literature on social policy and child protection by critically examining the paradox between quantitative policy success and the qualitative experiences of children as policy subjects. The novelty of this research lies in highlighting the gap between statistical reduction of street children and the actual quality of rights-based protection in a medium-sized city context in Eastern Indonesia. Strengthening rights-based implementation, institutional capacity, and participatory approaches is therefore essential to ensure sustainable child protection.